2004
DOI: 10.1038/ncb1096
|View full text |Cite
|
Sign up to set email alerts
|

Abl-dependent tyrosine phosphorylation of Sos-1 mediates growth-factor-induced Rac activation

Abstract: The non-receptor tyrosine kinase Abl participates in receptor tyrosine kinase (RTK)-induced actin cytoskeleton remodelling, a signalling pathway in which the function of Rac is pivotal. More importantly, the activity of Rac is indispensable for the leukaemogenic ability of the BCR-Abl oncoprotein. Thus, Rac might function downstream of Abl and be activated by it. Here, we elucidate the molecular mechanisms through which Abl signals to Rac in RTK-activated pathways. We show that Sos-1, a dual guanine nucleotide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
120
0
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(123 citation statements)
references
References 27 publications
1
120
0
2
Order By: Relevance
“…The mechanism by which Crk phosphorylation by Abl results in Rac activation may involve the recruitment of the Crk-binding protein DOCK180, a guanine nucleotide exchange factor (GEF) for Rac (37). Alternatively, Abl may activate Rac by phosphorylating Sos-1, which was reported to stimulate the Rac-GEF activity of Sos-1 (14).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanism by which Crk phosphorylation by Abl results in Rac activation may involve the recruitment of the Crk-binding protein DOCK180, a guanine nucleotide exchange factor (GEF) for Rac (37). Alternatively, Abl may activate Rac by phosphorylating Sos-1, which was reported to stimulate the Rac-GEF activity of Sos-1 (14).…”
Section: Discussionmentioning
confidence: 99%
“…The Abl kinases regulate a variety of cytoskeletal processes downstream of receptor tyrosine kinases and integrins (9)(10)(11)(12)(13)(14). We have shown that Abl kinases play a role in the regulation of intercellular signals at the neuromuscular junction (NMJ) and at sites of contact between invading bacterial pathogens and mammalian host cells (9,15).…”
mentioning
confidence: 99%
“…It has been shown that several GEFs activate Rac1 in response to EGF and PDGF signaling [13,[23][24][25]. To determine which exchange factors activate Rac1 downstream of VEGF, we first investigated the endogenous expression of candidate Rac1 GEFs in endothelial cells.…”
Section: Exchange Factor Vav2 Couples Vegf Signaling To Rac1mentioning
confidence: 99%
“…We and others have shown that endogenous Abl kinases are rapidly activated after EGFR stimulation (18 -20). Abl kinases are required for EGF-mediated membrane ruffling and Rac activation at physiological concentrations of the ligand (21). Moreover, the SH2 domains of Abl1 and Abl2 have been shown to bind with high affinity to the EGFR and other ErbB family members by interacting with multiple tyrosines on the phosphorylated receptors (19,22).…”
Section: Ligand-induced Endocytosis Of the Epidermal Growth Factor Rementioning
confidence: 99%